2013
DOI: 10.1021/la402630s
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Access: On the Nature of Adsorption/Desorption Hysteresis in Amorphous, Microporous Polymeric Materials

Abstract: The phenomenon of low-pressure adsorption/desorption hysteresis, which is commonly observed in microporous polymers, is investigated by detailed gas adsorption studies. Diffusional limitations by pore blocking effects, which arise as a consequence of the micropore morphology and connectivity, are discussed as the origin of the hysteresis rather than swelling effects, which have been suggested previously. Micropores with narrow openings, which cannot be filled easily, are expected to be present next to open por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
128
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(142 citation statements)
references
References 46 publications
14
128
0
Order By: Relevance
“…Such an abnormal dualmode isotherm has been reported for polymeric samples by Van der Vegt et al (2010) and associated to swelling effect (formation of new pores and dissolution of gas molecules in dense matrix). Jeromenok and Weber have associated this effect to the increased solvation pressure in the matrix, which acts as the driving force for filling the pores with restricted access (Jeromenok and Weber 2013). In the present case, the dual-mode isotherm of the sample can be associated to its typical morphology, formed by the interconnection or aggregation of small nanoparticles.…”
Section: Raman Spectroscopic Studymentioning
confidence: 67%
“…Such an abnormal dualmode isotherm has been reported for polymeric samples by Van der Vegt et al (2010) and associated to swelling effect (formation of new pores and dissolution of gas molecules in dense matrix). Jeromenok and Weber have associated this effect to the increased solvation pressure in the matrix, which acts as the driving force for filling the pores with restricted access (Jeromenok and Weber 2013). In the present case, the dual-mode isotherm of the sample can be associated to its typical morphology, formed by the interconnection or aggregation of small nanoparticles.…”
Section: Raman Spectroscopic Studymentioning
confidence: 67%
“…In these experiments Fig. 22,40,41 This experiment indicated that the degassing procedure (under vacuum at 80 C) may have resulted in kinetic pore closure assisted by the physical crosslinking of the pyrene. the equilibration intervals were increased in order to address the incomplete equilibration observed in our earlier N 2 isotherms (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The reason for the differences might be a result of the different sterical demands of the monomers included in the networks. The hysteresis in the low pressure range of both networks is indicative of the presence of restricted-access pores 63 and to the swelling of the network during the gas uptake. The latter one is probably also responsible for the small hysteresis observable for all CO 2 isotherms (Fig.…”
Section: Gas Sorption Propertiesmentioning
confidence: 99%